Involvement of the central nervous system in neuroblastomas: A potential direct pathway. (March 2020) - Odone-Filho, Vicente; Cristofani, Lilian Maria; Maluf, Paulo Taufi; Almeida, Maria Tereza Assis; Halley, Nathalia; Vince, Carolina Sgarioni Camargo; de Azambuja, Alessandra Milani Prandini; Brumatti, Melina; Lubraico, Priscilla; da Camara Lopes, Luiz Heraldo Arouche; Leite, Katia Ramos Moreira; Silva, Joao Luis Fernandes; et al.
Abstract: Although frequently disseminated to other anatomical sites, neuroblastoma (NB) is rarely reported as involving the central nervous system (CNS), which may reflect insufficient research in poorly controlled systemic disease. Here we demonstrate the involvement of the CNS in patients with NB over 18 months of age at diagnosis of extensive systemic disease. Meningeal metastases were observed even in the presence of complete systemic control. Although no improvement in patient's survival was observed, radiotherapy was effective in preventing CNS recurrence after observation of actual or previous dural disease. In conclusion, this study uncovered the uncommon pathologic involvement of the CNS in children with advanced NB and underscores the meningeal surface as a potential pathway for this to occur.